Felietonowość „Szkła Kontaktowego” - Grzegorzewski, Krzysztof (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
Analysis is dedicated to popular TV program “The Contactlense”. This program has nearly the biggest popularity among the watchers of TVN24 (the opinion-setting TV Station) and constitutes curious and original form of TV magazine. Author analyses its generic determinants and makes an attempt to put a generic diagnosis – which genre is nearest to “Contactlense” and which characters allow to say about its feuilletonic aspect. Text includes also observation about all the interactive elements and its generic role. Furthermore, “Contactlense” is seen as a trendsetter amongst TV magazines and could be interesting discussion subject.